2016
DOI: 10.1109/jstqe.2015.2490550
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Wideband Wavelength Conversion in Foundry-Compatible Silicon Waveguides Covered With Graphene

Abstract: We numerically examine the opportunities for wideband wavelength conversion through four-wave mixing (FWM) in a foundry-compatible 220 nm-thick silicon-on-insulator (SOI) waveguide covered with the highly nonlinear two-dimensional material of graphene. As a case study, we consider a foundrycompatible SOI waveguide shaped as a double spiral and covered with two separate graphene sheets, which are covered in turn by two solid polymer electrolyte gates. When combining subwatt level pump powers with a short wavegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
1
19
0
3
Order By: Relevance
“…For a Fourier-transformed ampli-tudeÃ(z, ω − ω 0 ) centered at frequency ω 0 , the square of the rms spectral width can be written as [11,12], which in the time domain can be expressed as [11]. For the experiments reported in this Letter, the pulse propagation is mostly determined by Kerr-nonlinear effects rather than dispersion and free-carrier effects (which was also verified numerically with the inclusion of graphenegenerated free carriers [12,13]). Hence, we can adopt a simplified version of the nonlinear Schrödinger equation incorporating only SPM effects and linear loss: ∂ z A = −(α/2)A + iγ K |A| 2 A, with γ K the Kerr nonlinearity and α the linear loss coefficient.…”
Section: Basic Principles Of Chirped-pulse-pumped Spmsupporting
confidence: 54%
See 1 more Smart Citation
“…For a Fourier-transformed ampli-tudeÃ(z, ω − ω 0 ) centered at frequency ω 0 , the square of the rms spectral width can be written as [11,12], which in the time domain can be expressed as [11]. For the experiments reported in this Letter, the pulse propagation is mostly determined by Kerr-nonlinear effects rather than dispersion and free-carrier effects (which was also verified numerically with the inclusion of graphenegenerated free carriers [12,13]). Hence, we can adopt a simplified version of the nonlinear Schrödinger equation incorporating only SPM effects and linear loss: ∂ z A = −(α/2)A + iγ K |A| 2 A, with γ K the Kerr nonlinearity and α the linear loss coefficient.…”
Section: Basic Principles Of Chirped-pulse-pumped Spmsupporting
confidence: 54%
“…with γ SOI,weighted and γ gr,weighted the weighted nonlinearity contributions from the underlying SOI waveguide and the graphene top layer, respectively. v p and I p are scaling factors defined in [13], ǫ 0 is the dielectric permittivity, ω p is the pump frequency, χ is the third-order Kerr-nonlinear conductivity of graphene. The latter can be converted to a susceptibility using χ = σ/(−iωǫ 0 d gr ) [19].…”
mentioning
confidence: 99%
“…3 in Ref. [13]). The majority of experiments have been performed in weakly doped graphene at high frequencies (near-IR, visible), where ω ≫ 2|E F |.…”
mentioning
confidence: 91%
“…Quantitatively, the theory predicts about one order of magnitude larger response than was experimentally observed (this contrasts to a number of previous publications, where the measured nonlinear response was claimed to be larger than the theoretically calculated one, see discussions in Refs. [3,4,13]). This discrepancy should be subject to further investigation.…”
mentioning
confidence: 99%
“…In our previous study, we demonstrated a large Kerr coefficient of graphene (n 2 ∼10 −12 m 2 · W −1 ), which is 6 orders of magnitude larger than that of silicon [14]. Combining graphene with silicon photonic devices offers a possible solution towards high-efficiency and broadband FWM [15,16]. Nevertheless, the high absorption of the graphene sheet greatly limits the performance of the FWM in the silicon-graphene hybrid devices [17].…”
Section: Introductionmentioning
confidence: 98%